Postoperative Recovery After Adult Spinal Deformity Surgery. Issue 19 (1st October 2015) - Scheer, Justin K.; Mundis, Gregory M.; Klineberg, Eric; Hart, Robert A.; Deviren, Vedat; Nguyen, Stacie; Protopsaltis, Themistocles S.; Gupta, Munish; Bess, Shay; Shaffrey, Christopher I.; Schwab, Frank; Lafage, Virginie; et al.
<x xml:space="preserve">Abstract</x> Study Design. Retrospective review of a multicenter, prospective adult spinal deformity (ASD) database. Objective. We hypothesized that increased age and increased preoperative disability would negatively impact both the length of time needed to achieve maximal recovery and the amount of functional improvement achieved. In order to gauge the recovery process, a normalization process was used to calculate an integrated health state (IHS) during the 2-year postoperative period. Summary of Background Data. Elderly patients with ASD generally have worse baseline health-related quality of life (HRQOL) measures than younger patients. Current methods of reporting outcomes are limited, perhaps diminishing the health impact of the entire postoperative recovery experience. Methods. Inclusion criteria included 18 or more years and ASD. Patient groups: young (⩽45 yr), middle (46–64), elderly (≥65) as well as by baseline Oswestry Disability Index (ODI) scores: MILD (0–30), MEDIUM (31–49), and HIGH (≥50). Collected HRQOL measures included ODI, Short Form-36(PCS/MCS), and Scoliosis Research Society-22 (SRS22) at baseline, 6 weeks, 1, and 2-year postoperative. All HRQOL measures were normalized to each patient's baseline scores. A 2-year IHS was calculated for each individual patient and the means were compared between groups. Results. 149 patients were included (⩽45:32, 46–64:67, ≥65:50). All groups significantly improved in all HRQOL at 2-year compared with baseline (P < 0.05) except for MCS, ODI, and SRS activity for the 45 or less group (P > 0.05). Normalized IHS HRQOL for young patients was worse than elderly for ODI, PCS, MCS, SRS activity, pain and total during the 2-year recovery period from index surgery. The MILD ODI group had significantly worse 2-year IHS values than the HIGH group for all HRQOL measured (P < 0.05) except SRS appearance and satisfaction (P > 0.05). Conclusion. Contrary to our hypothesis, an IHS analysis suggested that the recovery process was significantly better for elderly patients than young patients and better for patients with high baseline disability. Level of Evidence: 3